Co-variability of daily milk production traits, haematological and biochemical parameters in the blood serum and milk of Holstein cows - Franjo Poljak; Marcela Šperanda; Marija Špehar; Mislav Đidara; Vesna Gantner (Mljekarstvo)
Aiming to determine the variability and co-variability of daily production traits and biochemical as well as haematological parameters, blood and milk were taken from 25 Holstein cows during a three-month period, on a monthly basis. Thereby differences in analysed parameters due to the animal’s health status (acidosis or ketosis risk or normal health status; defined accordingly to fat/protein ratio) were determined. According to the statistical analysis, the co-variability level varied depending on the set of the analysed traits (from negligible to strong). The determined differences between the analysed biochemical and haematological parameters due to the animal's health status were not statistically significant. The obtained results indicate that the analysed biochemical and haematological parameters cannot be used as accurate indicators of acidosis prevalence, while for indication of ketosis prevalence, glucose and urea content in blood, sedimentation after 24 hours, as well as protein and iron content in milk, could be used. Furthermore, test-day records could be used as a valuable indicator of the prevalence risk of metabolic disorders (acidosis/ketosis) but for unambiguous detection in animals with the indication of a prevalence risk, other diagnostic methods should be used.